2002
DOI: 10.1002/polb.10216
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and structural characterizations of [chromophore]+‐saponite/polyurethane nanocomposites

Abstract: In this study, three chromophores-p-nitroaniline, 4-(4-nitrophenylazo)aniline, and 4-[(E)-2-{4-[(E)-2-(4-nitrophenyl)-1-diazenyl]phenyl}-1-diazenyl]anilinewere intercalated into layered aluminosilicate saponite and then dispersed into the polyurethanes matrix. The intercalated chromophore/saponite complexes were examined by inductively coupled plasma emission and element analysis technologies. The molecular orbital package computation simulation and X-ray diffraction (XRD) analysis showed that possible configu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…In such approach polymer nanocomposites are of great interest [2], and some interesting multifunctionalities are reported such optical sensors using colour sensitive gelatine pH indicator [3], or non-linear optical polymer using a saponite chromophore hybrid material into polyurethane [4]. We surmise that hybrid inorganic organic I/O assembly constitutes a suitable approach for obtaining multifunctional materials which can be subsequently used as filler for polymers [5], and more specifically, we focus here on the dual mechanical and optical properties supplied by a filler into a polymer.…”
Section: Introductionmentioning
confidence: 99%
“…In such approach polymer nanocomposites are of great interest [2], and some interesting multifunctionalities are reported such optical sensors using colour sensitive gelatine pH indicator [3], or non-linear optical polymer using a saponite chromophore hybrid material into polyurethane [4]. We surmise that hybrid inorganic organic I/O assembly constitutes a suitable approach for obtaining multifunctional materials which can be subsequently used as filler for polymers [5], and more specifically, we focus here on the dual mechanical and optical properties supplied by a filler into a polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Ring-opening polymerization of silicon-bridged ferrocenophanes provided access to the first examples of high molecular weight poly(ferrocenylsilanes) (PFS), which are useful materials for modification of electrodes as electrochemical sensors and as nonlinear optical materials. 6 -9 Wang et al 3 and Nguyen et al 10 have reported the detailed electrochemical studies for films of PFS.…”
Section: Introductionmentioning
confidence: 99%
“…Plenty of studies have already been conducted regarding polyurethane nanocomposites based on cast and thermoplastic elastomers [8][9][10][11][12][13][14] but there is no paper available to date concerning millable polyurethane-based nanocomposites. This paper highlights the preparation and the properties of the millable polyurethane/organoclay nanocomposite.…”
Section: Introductionmentioning
confidence: 99%